Bulletin. - Library of Congress. Copyright Office (Washington, Copyright Office, Library of Congress [for sale by the Supt. of Docs., U.S. Govt. Print. Off.], 1898)
Includes: Decisions of the United States Courts involving copyright.
Mode of access: Internet.
From 1898-1930: "Prepared by Thorvald Solberg, register of copyrights."
Nos. 17-37, 1909-1970. 1 v.
Keywords: Copyright